IMPLEMENTATION OF THE MASSED PRACTICE LEARNING METHOD IN IMPROVING DRIVE LEARNING OUTCOMES IN TABLE TENNIS GAMES IN IX A CLASS STUDENTS OF SMP NEGERI 24 MAKASSAR - Wahyu Munandar (Hanoman Journal: Physical Education and Sport, 2023)
This research is a classroom action research (CAR). This research was carried out in two cycles, each cycle consisting of three meetings. This study aims to improve the learning outcomes of drive in table tennis games through the massed practice learning method in table tennis games in the class IX A SMP Negeri 24 Makassar. The massed practice method is a continuous repetition of movements without interspersed with rest periods for a predetermined time. This research was conducted in two cycle stages consisting of 3 meetings in each cycle. There were 12 students with a percentage of 57.14% who did not meet the Minimum completeness criteria and 9 students with a percentage of 42.86% who met the Minimum completeness criteria in cycle one. Then in cycle II there was an increase in the learning outcomes of drive, namely only 1 student who did not meet the minimum completeness criteria with a percentage of 4.76% and 20 students who had fulfilled the Minimum completeness criteria with a percentage of 95.24%.